Zagadnienie metodologii badań w naukach historycznych i medycznych – problem interdyscyplinarności - Rybińska, Aleksandra (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
Nowadays, interdisciplinary research is becoming more popular. With his problem has to face many researchers. The specificity of the test procedures across the various fields different from each other. There are ranges of research that are difficult to classify into one cognitive methods. As a PhD student of history at the University of Lodz, who wrote the work in the history of medicine in the military health care in the years 1918–1939, I encountered such a problem. Status of medicine in my research method is a humanist. I decided to your thoughts and experiences in the field of learning and research in these two areas to collect and present, as a single text in the form of a scientific paper. The term research methodology understand the science of measurement method occurring phenomena, which the researcher wants to measure. It is a certain set of rules on how to study, who examine, then examine where to study. The aim of the research is to develop a methodology for better and better ways of measuring / testing phenomena ongoing improvement. The better method is the more accurate test results are obtained. The key to a reliable measurement of the phenomenon of interest to us is the selection of appropriate research methods / techniques of measurement. Each branch of science has developed and are developing their own research methods, in order to best measure the phenomena of interest to them. The purpose of my paper is to present, differences and similarities in medical science research methodology and historical sciences. The appearance of a “human face medicine”. I want to show you how to: we historians perceive problems in medicine (medical history), and how we deal with science, which is considered to be close. Two seemingly different environments, and having a lot in common.